1994
DOI: 10.1152/ajpcell.1994.267.5.c1210
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variations in local spike propagation in the myometrium of the 17-day pregnant rat

Abstract: Detailed spatial analysis of propagation of individual action potential was performed during spontaneous bursts of activity in the isolated 17-day pregnant rat myometrium. Use was made of high-resolution mapping with simultaneous recordings from 240 extracellular electrodes. Positioning of the electrode assembly by itself did not have any adverse effects, and no differences were found in the period or duration of spontaneous bursts recorded with and without the electrode assembly touching the tissue. The sprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
68
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(74 citation statements)
references
References 0 publications
6
68
0
Order By: Relevance
“…As also indicated in previous studies (8,9,19), the rat myometrium shows a relatively stable pattern of burst activity interspaced with a period of quiescence. In the guinea pig uterus, however, in vitro, there does not seem to be any regularity in frequency or type of contraction.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…As also indicated in previous studies (8,9,19), the rat myometrium shows a relatively stable pattern of burst activity interspaced with a period of quiescence. In the guinea pig uterus, however, in vitro, there does not seem to be any regularity in frequency or type of contraction.…”
Section: Discussionsupporting
confidence: 80%
“…The electrophysiology experiments were performed similar to those published previously (17,19). In summary, eight virgin Wistar rats were placed with a male overnight, and pregnancy was dated the next morning if sperm cells were observed in the vaginal lavage as day 0 of gestation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Miller et al (25) analyzed spike propagation in pregnant uterine segments that were 3 ϫ 1 cm in size and showed that velocity in the longitudinal direction was much faster than in the circumferential direction. Lammers et al (20) found similar results in equally small segments (8 ϫ 2 cm). Most of these studies were performed on isolated segments of myometrium, but a few studies have recorded from a limited number of electrodes in the whole intact myometrium in vivo.…”
mentioning
confidence: 58%
“…Due to a lack of evidence [19], many authors concluded that no classical linear propagation of single APs, similar to the myocardium, could be assumed for the myometrium, and that only a global propagation of the whole burst envelop could be measured [19], [20]. However, more recently, extensive measurements of the electrical activity of the guinea pig uterus using a grid of extracellular electrodes clearly demonstrated that also for the myometrium, similarly to the myocardium, a linear propagation of single electrical spikes occurs and can be measured [12], [21], [22].…”
Section: A Backgroundmentioning
confidence: 99%